When temporary agency work is not so temporary - Chambel, Maria José (2018)
Theory and empirical research have provided mixed arguments and evidence for the effects of temporary agency work on workers’ well-being. One unresolved issue is how length of service in agency work affects workers’ well-being and behaviour. This study, based on Self-Determination theory, explored this question by comparing the motives for temporary agency employment and the well-being of workers who have had this employment status for different periods of time. From a sample of 3300 Portuguese temporary agency workers, the study compared three groups who had been engaged in temporary agency work for (1) up to 6 months, (2) between 7 and 12 months and (3) between 13 and 24 months. Regression analyses, controlling for background variables and job insecurity perception, showed that longer periods of temporary agency working were associated with lower autonomous and voluntary motives for temporary employment, workplace well-being and well-being outside work. Theoretical and practical implications are discussed.